Essentials of psychological testing - Urbina, Susana (Hoboken, N.J. : John Wiley & Sons, 2004)
Packaged in the popular Essentials format, this book introduces the fundamental information needed to understand this vastly complex, technical, and dynamic field. Its unique coverage of psychometrics basics is broad and presented in an engaging style.
Includes bibliographical references and index.
Keywords: Psychological tests; Psychometrics